MORALITY AND NOBILITY: ETHICAL IMPLICATIONS IN MODERN SOCIETY - Jorovlea, Elvira; Codreanu, Alina (SWorld-Ger Conference proceedings, 2024)
In contemporary society, the concepts of morality and nobility are becoming increasingly intricate due to varying societal norms, cultural diversity, and individual experiences. Morality is influenced by multiple domains, including law, economy, and scie